In Silico Proof of the Effect of Quercetin and Umbelliferone as Alpha-Amylase Inhibitors, Which Can Be Used in the Treatment of Diabetes - ALTUNER, Ergin Murat (Kastamonu University, 2022)
Aim of study: The aim of this study is to show the in silico evidences about the potential use of quercetin and umbelliferone as α-amylase inhibitors, which is important for the treatment of diabetes. Material and methods: The possible conformations and orientations of quercetin, umbelliferone, and acarbose, in binding to the active sites of alpha-amylase, were analysed by CASTp server. The molecular dockings of these compounds to the potential active site were performed by AutoDock Tools to obtain 3D interactions and binding energies. In addition, the interaction scores were calculated by iGEMDOCK. The 2D enzyme-inhibitor interactions, which clearly show the interactions at the active sites, were analysed by LigPlot+. The drug-likeness properties of quercetin and umbelliferone were compared to acarbose by DruLiTo software and SWISSADME server. The absorption, distribution, metabolism, excretion, and toxicity (ADMET) scores, which present the pharmacokinetic properties of the compounds were analysed by ADMETLab, admetSAR, and PreADMET servers Main results: As a result, the α-amylase inhibitor activity and the potential use of quercetin and umbelliferone were proved in silico. Highlights: The results of the study clearly put forward that quercetin and umbelliferone could have possible medicinal use in the treatment of diabetes
Keywords: 3. Good health